Evaluation of Antioxidant and α-glucosidase Inhibitory Activities of Codonopsisjavanica (Blume) Hook. f. Thoms’ Root Extract - Thi Thuy, Nguyen; Ha Linh Trang, Ngo; Thi Thanh Binh, Nguyen; Thanh Tung, Bui (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 36 No 3, 2020)
This study aims to evaluate the antioxidant ability and α -glucosidase inhibitory activities of Codonopsisjavanica extract to elucidate its mechanism in the treatment of diabetes type 2. The roots of Codonopsisjavanica were extracted with ethanol solvents and fractionated with n -hexane, ethyl acetate and butanol solvents. The total extract and the fractions were evaluated for free radical scavenging by 2.2-diphenyl-1-picrylhydrazyl method and α -glucosidase inhibitory activity in vitro. The study results show that ethyl acetate fraction from Codonopsisjavanica roots had the strongest antioxidant activity with a value of IC 50 of 80.6 ± 2.8 µg/mL and a strong α -glucosidase enzyme inhibitory activity with a value of IC 50 of 80.4 ± 5 µg/mL. These data suggest that ethyl acetate fraction from Codonopsisjavanica roots may have potential for the prevention and treatment of diabetes type 2. Keywords Codonopsisjavanica, diabetes type 2, α -glucosidase, antioxidant ability, fraction. References [1] B.Y. Te. Guidelines for the diagnosis and treatment of type 2 diabetes, 2017. [2] U. Asmat, K. Abad, K. Ismail. Diabetes mellitus and oxidative stress-A concise review. Saudi pharmaceutical journal 24(5) (2016) 547. [3] D.K. Thu, V.M. Hung, N.T. Trang, B.T. Tung. Study on α-glucosidase enzyme inhibitory activity and DPPH free radical scavenging of green coffee bean extract (Coffea canephora). VNU Journal of Science: Medical and Pharmaceutical Sciences 35(2) (2019). [4] C.Y. Li, H.X. Xu, Q.B. Han, T.S. Wu. Quality assessment of Radix Codonopsis by quantitative nuclear magnetic resonance. Journal of Chromatography A 1216(11) (2009) 2124. [5] S.M. Gao, J.S. Liu, M. Wang, T.T. Cao, Y.D. Qi, B.G. Zhang, et al. Traditional uses, phytochemistry, pharmacology and toxicology of Codonopsis: A review. Journal of ethnopharmacology 219((2018) 50. [6] T.T. Ha, H.V. Oanh, D.T. Ha. Chemical constituents of the n-butanol fractions from the roots of Vietnamese Codonopsis javanica (Blume) Hook.f. Journal of Pharmacy 56(4) (2016). [7] T.T. Ha, N.M. Khoi, N.T. Ha, N.V. Nghi, D.T. Ha. Chemical Constituents from Roots of Codonopsis javanica (Blume) Hook.f. Journal of Medicinal Materials 19((2014) 211. [8] B.T. Tung, D.K. Thu, N.T.K. Thu, N.T. Hai. Antioxidant and acetylcholinesterase inhibitory activities of ginger root (Zingiber officinale Roscoe) extract. Journal of Complementary and Integrative Medicine 14(4) (2017). [9] B.T. Tung, D.K. Thu, P.T. Hai, N.T. Hai. Evaluation of α-glucosidase inhibitory effects of Pomegranate fruit extracts (Punica granatum Linn). Journal of Traditional Vietnamese Medicine and Pharmacy 5(18) (2018) 59. [10] F. Moradi-Afrapoli, B. Asghari, S. Saeidnia, Y. Ajani, M. Mirjani, M. Malmir, et al. In vitro α-glucosidase inhibitory activity of phenolic constituents from aerial parts of Polygonum hyrcanicum. DARU Journal of Pharmaceutical Sciences 20(1) (2012) 37. [11] D.T. Bao. Free radicals. Journal of Pharmacy 6((2001) 29. [12] M. Carocho, I.C. Ferreira. A review on antioxidants, prooxidants and related controversy: natural and synthetic compounds, screening and analysis methodologies and future perspectives. Food and chemical toxicology 51((2013) 15. [13] National Institute of Medicinal Materials. Method for studying the pharmacological effects of herbal drugs. Science and Technology Publishing House, 2006. [14] J.W. Baynes. Role of oxidative stress in development of complications in diabetes. Diabetes 40(4) (1991) 405. [15] S.M. Jeon, S.Y. Kim, I.H. Kim, J.S. Go, H.R. Kim, J.Y. Jeong, et al. Antioxidant activities of processed Deoduck (Codonopsis lanceolata) extracts. Journal of the Korean Society of Food Science and Nutrition 42(6) (2013) 924. [16] C.S. Yoo, S.J. Kim. Methanol extract of Codonopsis pilosula inhibits inducible nitric oxide synthase and protein oxidation in lipopolysaccharide-stimulated raw cells. Tropical Journal of Pharmaceutical Research 12(5) (2013) 705. [17] J.Y.W. Chan, F.C. Lam, P.C. Leung, C.T. Che, K.P. Fung. Antihyperglycemic and antioxidative effects of a herbal formulation of Radix Astragali, Radix Codonopsis and Cortex Lycii in a mouse model of type 2 diabetes mellitus. Phytotherapy Research: An International Journal Devoted to Pharmacological and Toxicological Evaluation of Natural Product Derivatives 23(5) (2009) 658. [18] S. Kumar, S. Narwal, V. Kumar, O. Prakash. α-glucosidase inhibitors from plants: A natural approach to treat diabetes. Pharmacognosy reviews 5(9) (2011) 19. [19] K. Tadera, Y. Minami, K. Takamatsu, T. Matsuoka. Inhibition of α-glucosidase and α-amylase by flavonoids. Journal of nutritional science and vitaminology 52(2) (2006) 149. [20] C.W. Choi, Y.H. Choi, M.-R. Cha, D.S. Yoo, Y.S. Kim, G.H. Yon, et al. Yeast α-glucosidase inhibition by isoflavones from plants of Leguminosae as an in vitro alternative to acarbose. Journal of agricultural and food chemistry 58(18) (2010) 9988. [21] K. He, X. Li, X. Chen, X. Ye, J. Huang, Y. Jin, et al. Evaluation of antidiabetic potential of selected traditional Chinese medicines in STZ-induced diabetic mice. Journal of ethnopharmacology 137(3) (2011) 1135. [22] S.W. Jung, A.J. Han, H.J. Hong, M.G. Choung, K.S. Kim, S.H. Park. alpha-glucosidase inhibitors from the roots of Codonopsis lanceolata Trautv. Agricultural Chemistry and Biotechnology 49(4) (2006) 162. [23] R. Gupta, A.K. Sharma, M. Dobhal, M. Sharma, R. Gupta. Antidiabetic and antioxidant potential of β‐sitosterol in streptozotocin‐induced experimental hyperglycemia. Journal of diabetes 3(1) (2011) 29. [24] R. Khanra, N. Bhattacharjee, T.K. Dua, A. Nandy, A. Saha, J. Kalita, et al. Taraxerol, a pentacyclic triterpenoid, from Abroma augusta leaf attenuates diabetic nephropathy in type 2 diabetic rats. Biomedicine & Pharmacotherapy 94((2017) 726. [25] A.I. Alagbonsi, T.M. Salman, H.M. Salahdeen, A.A. Alada. Effects of adenosine and caffeine on blood glucose levels in rats. Nigerian Journal of Experimental and Clinical Biosciences 4(2) (2016) 35. [26] A.M. Mahmoud, O.E. Hussein. Hesperidin as a promising anti-diabetic flavonoid: the underlying molecular mechanism. Int J Food Nutr Sci| Volume 3(3) (2014) 1.